Inventorying the ichthyologic fauna of Ahémé Lake and its Channels (South-West Benin, West Africa) - Viaho, Christian Comlan; Lederoun, Djiman; Agblonon Houelome, Thierry Matinkpon; ADANDEDJAN, Delphine; Ahouansou Montcho, Simon; Agadjihouèdé, Hippolyte; Gbedey, Martin; LALEYE, PHILIPPE A. (My University, 2020)
The present study aims at contributing to a better understanding of Lake Ahémé and its surroundings together with its channels through an update of its fish fauna. The study covers twelve months, from May 2016 to April 2017. Fish specimens which were examined were collected from catches by fishermen as well as from monthly experimental fishing at 19 stations. A total of 73 fish species belonging to 59 genera and 38 families were identified. The Gobiidae family is the most represented with 6 species; the Carangidae and Cichlidae families are next, with 5 species each; then comes the Clupeidae with 4 species; and the Eleotridae, Clariidae, and Lutjanidae families with 3 species each. Strictly estuarine species (E) dominate the population and account for 87.7% of the total species richness
Keywords: Inventorying; Fish fauna; Experimental fishing; Lake; Channels